Towards a regional urban agenda: approaches and tools - Federica Isola; Federica Leone; Cheti Pira (Regional Studies, Regional Science, 2017)
During the 2014–20 programming period concerning European structural and investment (ESI) funds, the urban dimension has assumed considerable importance within European Union Cohesion Policy. This shift aims at guaranteeing more coherence between European challenges and urban planning, and at using European funding in a more efficient way. The definition and implementation of an urban agenda has become a prerequisite to meet the objectives of sustainable economic development based on an integrated approach to urban policy. From this conceptual perspective, the collaboration and coordination efforts between different levels of government represents a key element. Therefore, the implementation of models of multilevel governance could promote sustainable and socially inclusive growth of European cities, and greater involvement and coordination of urban areas within decision-making processes. This paper addresses the integrated approach to sustainable urban development through a critical analysis of the implementation of integrated territorial investments (ITIs) in the case study of the Sardinian region of Italy to investigate whether ITI could serve as a tool for pursuing/implementing the urban agenda.